Morphofunctional features of thymus of twelve-month-old rats exposed to repeated hypergravity - Moroz G. A. (Морфологія, 2010)
Twelve-month-old male Wistar rats were exposed to hypergravity (9g, 10 minutes, daily, 30 and 45 times). Morphology of thymus was investigated. Hypergravity caused evident haemodynamic disturbances and involution in thymus after 30 exposures. Developing hypoxia and stress-response potentiated dystrophy of both lymphocytic and epithelial components of thymus. After 45 exposures dystrophic-destructive alterations prevailed in lymphoid tissue and stroma of organ against the background stable haemodynamic disturbances. Delymphatization of parenchyma increased, cutolitic reaction rised, cell migration activity was inhibited. This characterises failure of adaptation. Revealed disturbances depend on exposure multiplicity and are features of adaptive response of organism on hypergravity.